Toxicity test of Kedayan root infusion (Aristolochia sp.) using brine shrimp lethality test method - Syuhada Syuhada; Benazir Evita Rukaya; Budi Setiawan (Universitas Ahmad Dahlan, 2022)
Kedayan roots are still used by the Lundayeh Dayak people as traditional medicine. This plant is one of the Aristolochia sp. species whose production and distribution as traditional medicine or food supplements are prohibited by the Food and Drug Supervisory Agency of the Republic of Indonesia because it has side effects that are harmful to the body. The purpose of this study was to determine the toxicity of kedayan root infusion using the Brine Shrimp Lethality Test (BSLT) method based on the LC50 value. Toxicity test was carried out by varying the concentration of Kedayan root infusion, namely 100, 500, and 1000 ppm, as an intervention against Artemia salina Leach with a negative control in the form of 2.8% saline solution for 24 hours with 3 replications, then observing the presence or absence of movement of Artemia salina L. Larvae. Test results data in the form of % mortality obtained, then analyzed using the probit regression analysis method to determine the LC50 value. The results of this study indicate that the kedayan root infusion has very high toxicity, the LC50 value is 101.9278 ppm.